Variation in carotid interventional practice in ACST-2: 3600 patients randomised to CEA v CAS. (3rd October 2022) - Bulbulia, R; Halliday, A; Behalf Of Acst Collaborators, O N
Abstract: Introduction: For patients requiring revascularization for tight asymptomatic carotid stenosis, ACST-2 compared the hazards and long term benefits of carotid artery stenting (CAS) vs carotid endarterectomy (CEA). 3625 patients were enrolled; Italy, was the top recruiting country (24% of total), followed by the UK (13%). Methods: Patients joined ACST-2 when CEA and CAS were both possible, but where there was substantial uncertainty as to which procedure was most appropriate. Trial design was streamlined, with broad eligibility criteria and collaborating surgeons and stenters were free to use their usual techniques and CE approved devices. In this report, we compared the baseline characteristics and procedural techniques used for 867 Italian patients, 470 UK patients and 2288 participants from the Rest of the World (RoW). Results: Italian participants median age was 73 and around 5 years older than UK and RoW, and a greater proportion were women (34% Italy v 29% RoW and UK). Medical therapy at trial entry was good, but blood pressure control (SBP <140mmHg) was better in Italian patients and worst in the UK (70% Italy v 64% RoW v 47% UK). Intervention for moderate stenosis (<70%) was uncommon in Italy (1%) and the RoW (4%), but more frequent in UK (11%), possibly due to a higher rate of contra-lateral occlusion in UK patients (14%) compared with Italy (2%) and RoW (4%). Plaque echolucency was assessed more frequently in Italy (86%) and RoW (69%) than in the UK (29%), and amongst those assessed, the presence of echolucent plaques was the same in Italy and the RoW (49%), but less common in the UK (33%). Surgery under local anaesthetic was preferred in Italy (60%) but not in UK and RoW (30%). Use of a shunt was uncommon in Italian (14%) and RoW (16%) compared with UK (52%) as was patching (25% Italy v 42% RoW v 79% UK). Cerebral protection devices (CPD) were used in 99.5% Italian procedures, 80% in RoW but in only 68% of UK cases, with distal protection devices favoured. Proximal occlusion devices were used quite frequently in UK (40% of all CPD) and Italy (25%) but infrequently in RoW (12%). Closed cell stents were most commonly used and particularly favoured in Italian centres (54% v 46% RoW v 34% UK and), as was the use of newer membrane covered stents (19% Italy v 13% UK and 7% RoW). Conclusion: There was marked regional variation in patient characteristics and intervention techniques in ACST-2. Italian patients were older and more likely to be female. Surgery under local anaesthesia was much more common in Italy, and patching was common in UK and infrequent in Italy and RoW. During CAS, CPD use was almost universal in Italy, but less frequent in RoW and UK, and closed and membrane covered stents were more commonly used in Italian patients compared to UK and RoW. Large trials, like ACST-2, typically include a wide range patients and interventional techniques, and this can help make the long-term results of such studies generalizable. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): NIHR HTA, BUPA Foundation AND NDPH